2015
DOI: 10.1080/1540496x.2015.1039903
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Corporate Social Responsibility and Corporate Financial Performance in Korea

Abstract: This study examines the relationships between corporate social responsibility (CSR) and corporate financial performance (CFP) for the period 2004-2010 in Korea. This study performs difference generalized method of moments (GMM) estimation on a dynamic panel model. The results for the entire industry show CSR has a positive effect on CFP in Korea, and the stakeholder theory seems valid. Industry analysis shows different results by each industry's characteristics. The results also reveal the effect of CSR on CFP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 39 publications
5
41
0
4
Order By: Relevance
“…Researchers and academics that found a negative relationship between CSR and business performance, have argued that implementation costs of CSR are too high compared with the results obtained (Oh and Park, 2015). Among these investigations that found this type of results were those from Vance (1975); Balabanis et al (1998); Moore (2001); Brammer et al (2005) and Lopez et al (2007).…”
Section: Literature Reviewmentioning
confidence: 92%
See 1 more Smart Citation
“…Researchers and academics that found a negative relationship between CSR and business performance, have argued that implementation costs of CSR are too high compared with the results obtained (Oh and Park, 2015). Among these investigations that found this type of results were those from Vance (1975); Balabanis et al (1998); Moore (2001); Brammer et al (2005) and Lopez et al (2007).…”
Section: Literature Reviewmentioning
confidence: 92%
“…Corporate Social Responsibility (RSE) has been recognized in the current literature of business and management sciences, as one of the main constructs that in a coherent manner supports and strengthens the existing relationship between company and society (Oh and Park, 2015). As a prove of that is that the Organization for Economic Cooperation and Development (OECD) does not only established since mid seventies as a guideline about CSR for multinational companies (OECD, 1976) but also carried out a global convention against bribery, by mid nineties (OECD, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The relationship between corporate social responsibility (CSR) and financial performance (FP) has enjoyed a widespread debate among scholars [3]. The review of the empirical research leads to different conclusions, either regarding the existence of a positive link between CSR and FP [4][5][6], of a negative relationship [7], or even regarding the lack of a link [8] between these variables. The inconsistency is generally caused by the different measures used to cuantify CSR and FP, the heterogenous analysis techniques, the limitations of data (small sample sizes, old data), the features of the sampled companies (dimension, area of activity, affiliation to a developed or emerging market etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Weber et al (2010); Mishra and Suar (2010); Doh et al (2010) concluded that in the large percentage of existing literature scholars and researchers indicated that the adoption of CSR practices support the companies to enhance the level of performance. According to Demetriades and Auret (2014); Taiwo and Adeniran (2014) ;Oh, and Park (2015), within the last thirty years there were a considerable number of different theoretical and empirical research studies that analyzed and discussed the prevailing association of CSR and company performance.…”
Section: Corporate Social Responsibility (Csr) Practices and Businessmentioning
confidence: 99%